Effects of anodal transcranial direct current stimulation on intracranial compliance in the subacute phase of stroke - Nascimento, Monalisa Resende; Bernardes, Tiago Soares; Santos, Kelly Cristina Sousa; Silva, Gabrielly Fernanda; Bazan, Rodrigo [UNESP]; Sande de Souza, Luciane Aparecida Pascucci; Luvizutto, Gustavo José (Elsevier, 2024)
Objectives: Transcranial direct current stimulation (tDCS) increases cerebral blood flow. This study evaluated the effects of anodal tDCS (A-tDCS) on intracranial compliance (ICC) in patients with subacute stroke using a non-invasive method. Methods: This was a randomized, proof-of-concept, double-blind, pilot study. Patients with ischemic stroke of the middle cerebral artery (MCA) were divided into the following two groups: 1) A-tDCS in the motor cortex on the affected side for 30 min at 2 mA, and 2) sham tDCS in the motor cortex on the affected side. The primary outcomes were intracranial compliance (P2/P1 ratio and time-to-peak [TTP]) and ICC normalization after the intervention (P2/P1 ratio <1). Secondary outcomes were systolic and diastolic blood pressures, heart rate, and peripheral oxygen saturation. Results: No significant differences were observed in the P2/P1 ratio (P = 0.509) and TTP (P = 0.480) between the groups. However, the A-tDCS group was significantly associated with a normal P2/P1 ratio after intervention (B = 2.583; standard error [SE]: 1.277; P = 0.043; corrected for age and stroke severity). No significant associations were observed between the groups and systolic blood pressure (F = 0.16; P = 0.902), diastolic blood pressure (F = 0.18; P = 0.892), heart rate (F = 0.11; P = 0.950), or peripheral oxygen saturation (F = 0.21; P = 0.750). Conclusion: ICC morphology normalization was observed in the A-tDCS group. However, no differences were observed in the P2/P1 ratio, TTP, or hemodynamic variables between the groups. A sample size of 66 patients with ischemic stroke of the MCA can be estimated using the observed effect size and standard α = 5 % and β = 20 % for future trials. Furthermore, this will aid in conducting the necessary randomized trials targeting these populations.
Keywords: Intracranial compliance; Intracranial pressure; Non-invasive; Stroke; Transcranial direct current stimulation